2009
DOI: 10.3892/mmr_00000083
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan as a peroxisome proliferator-activated receptor-γ ligand is a new target in the treatment of human renal cell carcinoma

Abstract: Abstract. Angiotensin II receptor blockers (ARBs) are widely used as hypertensive therapeutic agents. However, it has been reported that Telmisartan (a type of ARB) additionally activates peroxisome proliferator-activated receptor (PPAR)-Á. We previously reported that PPAR-Á ligand induced the growth arrest of renal cell carcinoma (RCC) cells through apoptosis, and that Telmisartan had the potential to inhibit prostate cancer cell growth through apoptosis. In this study, we evaluated the effects of Telmisartan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…It has also been demonstrated that telmisartan induced apoptosis and DNA fragmentation in human urological cancer [8], [9], [29]. Here we found that treatment with telmisartan significantly increased the number of apoptotic cells in all endometrial carcinoma cell lines studied.…”
Section: Discussionsupporting
confidence: 77%
“…It has also been demonstrated that telmisartan induced apoptosis and DNA fragmentation in human urological cancer [8], [9], [29]. Here we found that treatment with telmisartan significantly increased the number of apoptotic cells in all endometrial carcinoma cell lines studied.…”
Section: Discussionsupporting
confidence: 77%
“…Telmisartan has been shown to inhibit cell proliferation by inducing apoptosis in various cancer cell lines, namely, prostate ( 8 ), renal ( 9 ), endometrial ( 6 ) and colon ( 10 ) cancer lines. To determine whether telmisartan induced apoptosis, HuCCT-1 cells were treated with or without 100 µ M telmisartan and analyzed using Annexin V-FITC/PI staining and measuring the levels of cCK18, but it did not induce apoptosis and cell death after telmisartan-treatment in HuCCT-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibited the growth of adult T-cell leukemia cell ( 5 ), endometrial ( 6 ), and gastric cancer cells ( 7 ) in several studies. The main mechanism associated with antitumor effect by telmisartan treatment has been shown to inhibit cell proliferation by inducing apoptosis in various cancer cell lines, including prostate ( 8 ), renal ( 9 ), endometrial ( 6 ) and colon ( 10 ) cancer lines. More recently, telmisartan induced cell cycle arrest in hematologic and non-hematologic malignancies including our study ( 5 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Telmisartan has been shown to inhibit cell proliferation by inducing apoptosis in various cancer cell lines, including endometrial [10], prostate [19], renal [20], and colon [21] cancer lines. To determine whether telmisartan induced apoptosis, we treated EAC cells with or without 100 μM telmisartan for 24 and 48 h and analyzed the cells using flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-γ activation inhibits cell growth in several cancers [1518]. Additionally, telmisartan inhibits the proliferation of various cancer cell types, including prostate [19], renal [20] and colon [21] cancer cells, by inducing apoptosis.…”
Section: Introductionmentioning
confidence: 99%